Estimating Pollutant Removal Requirements for Landfills in the UK: III. Policy Analysis and Operational Implications. - Hall, D. H.; Drury, D.; Gronow, Jan R.; Pollard, Simon J. T.; Smith, Richard (Taylor & Francis, 2007)
The policy analysis and management implications for achieving landfill equilibrium status within a sustainable timescale (decades rather than centuries) are presented based on modelled results reported previously. Until relatively recently, timescale estimates suggested that equilibrium or landfill completion could be achieved within 40-60 years i.e. the same order of magnitude as financial provision for aftercare. However results of modelling in this study (reported in previous paper) suggest that timescales may be considerably longer (many centuries in some instances) suggesting that financial provision may be inadequate. The role of the most promising and available waste treatment technologies and strategic waste management options in contributing towards achieving equilibrium status are discussed. Results suggest that a re- examination of techniques for accelerating landfill stabilisation, including aerobic and bioreactor landfill, is warranted.
Keywords: Equilibrium; Completion; Emissions; Municipal solid waste (MSW)